A CENTURY OF CONSTITUTIONALISM - Cornelia Beatrice Gabriela ENE-DINU (Challenges of the Knowledge Society)
In the exceptional framework at the end of the First World War, followed by the union with the Old Kingdom of the Romanian provinces of Bessarabia, Bucovina and Transylvania, the question of a new constitution was raised, to reflect the new political, economic-social, ethnic and institutional conditions. The problem of national minorities had also become more complex, confessions had appeared that previously were not very important from a numerical point of view in the Old Kingdom (Greek-Catholic, Protestant, Catholic), and through the peace treaties Romania was obliged to guarantee their rights. After the war, until January 1922, there were no less than six governments, three of which were led by generals (Arthur Văitoianu, Alexandru Averescu, Constatin Coandă), who did not elaborate such a vast and complicated work. The situation changed with the coming to the head of the government, on January 19, 1922, of the well-known politician Ion I.C. Brătianu, who had the ambition to complete what he had started en 1914 without bringing it to fruition. Becoming prime minister, Ion I.C. Brătianu proposes to the king the organization of elections for the National Constituent Assemblies, a name that wanted to highlight both their representative character for the nation and their role in the construction of the state.